The Rice Alms Movement in Strengthening Harmony Among Religious Communities in the Village of Tolerance - Achmad Faqihuddin; Faisal Fauzan Ilyasa; Abdillah Muflih; Iif Syarifudin; Sholachuddin Al-Ayyubi; Fajar Romadhon (Pusat Pengkajian dan Pengembangan Islam Jakarta (PPIJ), 2024)
Research conducted by the Ministry of Religious Affairs' Research and Development Agency (Balitbang Kemenag) in 2020, the Indonesian Survey Institute in 2022, and the Indonesian National Counterterrorism Agency in 2023 indicates that radicalism continues to be a significant issue in Indonesia, necessitating a variety of solution proposals to achieve harmony among religious communities. This study examines the social dynamics and interactions among religious communities within the context of the Rice Alms Movement in Kampung Toleransi, Bandung, Indonesia. Employing an ethnographic approach, the research aims to understand how the rice alms movement contributes to the development of social harmony and solidarity in a pluralistic society. The study subjects include five key roles in the community: the Neighborhood Association Head (Ketua RW), Religious Leaders, Community Leaders, Youth Leaders, and Academics. Data collection methods involved in-depth interviews, participatory observation, and document studies. Data analysis was performed using NVIVO 12 software. The findings indicate that the Rice Alms Movement has successfully strengthened solidarity and empathy among residents from diverse religious backgrounds, while also reducing economic disparities. The involvement of religious communities and the younger generation are key factors in the success of this movement. This research provides empirical evidence on the role of religious practices in promoting social harmony and tolerance among religious communities. Recommendations for enhancing the effectiveness and sustainability of the movement include developing a more organized management system, continuous educational programs, and collaboration with local government and non-governmental organizations. The findings of this study contribute to the academic understanding of the relationship between religion, social solidarity, and community development, and provide practical insights for similar initiatives in other pluralistic societies.